THE USE OF DUBBING VIDEO TECHNIQUE FOR STUDENTS’ ENGLISH-SPEAKING SKILLS AND SELF-CONFIDENCE - Alfiyanti, Rizki Muthiah; Samtidar, Samtidar; Korompot, Chairil Anwar (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This research aims to evaluate the effectiveness of using the Dubbing Video technique in improving students' English language skills and self-confidence at SMPN 21 Makassar. This research uses a quasi-experimental method with cluster random sampling technique. The samples chosen were class VIII F as the experimental class and class VIII G as the control class. The sample consisted of 28 experimental group students and 26 control group students. Data was collected through speaking tests and self-confidence questionnaires and analyzed using SPSS 27. The analysis of the paired sample t-test analysis showed a significance value (Sig. 2-tailed) < 0.001 for the experimental group, demonstrating a significant difference in speaking skills between students taught with the Dubbing Video technique and those who are not taught using this technique. The results showed a significant improvement in the experimental group. In speaking skills, the average score of the experimental group increased from 56.00 (pre-test) to 72.71 (post-test), while the control group only increased from 46.46 to 60.46. For self-confidence, the experimental group showed an increase from 66.29 to 79.68, while the control group increased from 60.54 to 71.88. So, it can be concluded that the Dubbing Video technique has proven to be effective in improving English speaking skills and self-confidence at SMPN 21 Makassar.Keywords: Dubbing Video; Speaking Skills; Self-confidence